PENDEKATAN KONSELING REALITA DALAM MENGINTERVENSI PERILAKU BULLYING - Bakhrudin All Habsy; Nindya Julisia; Ananda Mustika Putri; Niswa Tirta Ageng Dzakiyah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
Basically, every individual must want a basic need to be met, meaning that if this individual can meet his needs, it will be able to satisfy the individual. But on the contrary, if what is desired is not in accordance with the reality in life, it will make the individual depressed and may make him a problematic individual. Unfulfilled basic needs have three indicators, namely being unable to take responsibility for their choices, not being able to accept the logical consequences of an action and not having norms as guidelines or guidelines in acting according to right and wrong considerations.No exception for bullies, this can happen because of the unfulfilled need for power and fun. As a result, individuals meet these needs in the wrong way. Reality counseling comes as a suitable solution for bullying because in reality counseling individuals are encouraged to understand the wants, needs and expectations of their surroundings and understand the consequences of each of their actions.